DETERMINANTS ANALYSIS OF ENDEK WOVEN FABRIC PRODUCTION IN SIDEMEN DISTRICT, KARANGASEM REGENCY - Ni Komang Gayatri Primayogi; A.A. Ketut Ayuningsasi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The industrial sector plays a crucial and strategic role in the economy of a region, as its presence significantly contributes to the economic development of the area, including the traditional Endek weaving industry in Bali. This study aims to analyze the determinants of Endek fabric production in Sidemen District, Karangasem Regency. The research is a quantitative study with an associative design. The study was conducted in Sidemen District, Karangasem Regency. The population consists of 2,141 Endek weaving industries in the district, with a sample size of 96, selected using accidental sampling. Data collection was carried out through observation, interviews, literature study, and questionnaires. The analysis technique used is inferential analysis (multiple linear regression). The results of the study indicate that: 1) Capital, labor, government policies, and technology have a significant simultaneous effect on the production of Endek fabric in Sidemen District, Karangasem Regency; and 2) Capital, labor, government policies, and technology have a positive and significant partial effect on the production of Endek fabric in Sidemen District, Karangasem Regency. This study highlights the importance of empowering the local workforce to improve socioeconomic welfare while preserving the region's cultural heritage in Sidemen District, Karangasem Regency.